Pig embryonic stem cells with porcine specific-MSGN1 upstream region-based reporter system for monitoring paraxial mesoderm differentiation - Jinsol Jeong; Kwang-Hwan Choi; Dong-Kyung Lee; Yelim Ahn; Chang-Kyu Lee (Stem Cell Research)
Pig embryonic stem cells were introduced with an MSGN1 upstream region-based reporter system, composed of EGFP sequence under porcine-specific MSGN1 promoter (pMSGN1), through electroporation. The engineered cell line maintained pluripotency similar to that of the parental cell line, and reporter activity was confirmed upon the induction of the paraxial mesoderm. The pMSGN1-EGFP reporter system is a valuable tool for monitoring the differentiation process of the paraxial mesoderm and analyzing induction efficiency, providing insight into developmental mechanisms.